The role of infill building in the sustainable conservation Casestudy : Surabaya downtown - Bambang Soemardiono; Defry Agatha Ardianta (Institut Teknologi Sepuluh Nopember, 2017)
Most of the building in the conservation area in Surabaya are facing such dillematic situation. One side the heritage buildings should keep the architectural, historical, aesthetical as well as social values but in the other side they must be developed based on the real market demand. Infill building should be the solution in making respectful contemporary contribution to the conservation area. The result of this paper is to formulate a framework requirements of the development and suggest the role in form of model of infill building based on the sustainable conservation approach, so the development is not only solving the physical problems but also non-physical.